Leading with soul : examining the praxis of critical servant leadership theory and spiritual leadership for school administrators - Vassar, Rema Reynolds; Alston, Judy; Barnett, Clyde, III (Contemporary perspectives on spirituality in education., 2025)
This book aims to challenge what we consider to be static and superficial understandings of servant leadership within PreK-12 school communities. We highlight myriad ways servant leadership is misused and misunderstood within educational settings and contend that this misuse has led to a lack of moral leadership grounded in individual and collective conceptualizations of spirituality. Further, there is scant literature addressing both diverse manifestations of and the dearth of spiritual leadership within schools. Recent critical leadership theories have emerged to help leaders reflect on implications related to race and racism, gender (e.g., homophobia), and religion (e.g., Islamophobia). While critical reflections are difficult, they are imperative as, for example, Black boys and girls in special education and remedial courses are over-represented relative to their overall presence in schools. Additionally, Black students, both girls and boys, are disproportionately disciplined when compared to other racial groups, especially white students. With this book, we aim to definitively explore servant leadership toward an ontological understanding and operationalization of critical servant leadership; offering ideal school policy and practice to support it, providing examples of its manifestations within school communities, and articulating a vision for this theory's future. While many theorists acknowledge the necessity of culturally relevant, responsive, and congruent practices, they often proffer specific, discrete strategies and ideas to help facilitate these kinds of leadership. We disagree with offering leaders specific leadership strategies but argue rather that what is missing from what is now popular and mainstream professional development for leaders is the reflexive component that requires leaders to examine their own dispositions, practices, and biases, which ultimately can function as impediments to student learning. Moreover, we argue that most professional development purporting to "train" leaders fails to incorporate critical servant leadership and address the role of spirituality in leading public and charter K-12 schools.